Zmiany w poziomie dochodów gmin województwa pomorskiego w latach 1999-2004 - Sekuła, Alicja (Changes in Revenues Level of Pomeranian Voivodship Communes between 1999 and 2004, 2007)
The article presents an analysis of revenues of Pomeranian Voivodship communes. Due to very unstable law concerning functioning of territorial self-governments, especially their financial economy, the analyzed period was limited to 6 years (i.e. 1999-2004), which were - more or less - stable. Tlie research wasn't limited only to show the basic indications, i.e. the total budget revenues per capita or the shares of own revenues in total revenues, but it was also aimed at searching features that work in favour of their high levels.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 574-585